PENGEMBANGAN SEKOLAH RAMAH ANAK DI TINGKAT PENDIDIKAN ANAK USIA DINI - tusriyanto, tusriyanto (Ri'ayah: Jurnal Sosial dan Keagamaan, 2020)
The phase of children aged 0-6 years (golden age) is a period where children must get special education so that their physical and mental growth and development are appropriate in order to be able to receive and respond to stimulation obtained from the environment. The most important thing that must be carried out by the management of education, especially at the level of Early Childhood Education is to seek Child Friendly Schools. Child-friendly schools are defined as an open school concept, trying to apply learning that pays attention to students' psychological and psychological development. The development of SRA can be implemented in Early Childhood Education (PAUD), through collaboration from families, communities and schools.